2010
DOI: 10.1038/jes.2010.36
|View full text |Cite
|
Sign up to set email alerts
|

Residential insecticide usage in northern California homes with young children

Abstract: Residential insecticide usage and actual application details were collected in a population-based sample of 477 households residing within 22 counties in northern California with at least one child of age p5 years between January 2006 and August 2008. Structured telephone interviews were conducted collecting information on residential use of insecticides, including outdoor sprays, indoor sprays, indoor foggers, applications by professionals, and pet flea/tick control during the previous year. Interviews also c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
2
18
1
Order By: Relevance
“…Ventilation after treatment may reduce the concentration of chemical in the treated room and reduce dispersal [26], yet, our findings suggest that less than half of all individuals using indoor sprays are ventilating rooms during and after applying the sprays. These results are slightly different than the findings from the Northern California SUPERB survey of families with young children, in which 58% reported opening one or more windows during or after application of indoor sprays [16]. This difference could be due to age related factors, or could also be due to the difference in climate between Northern and Central California group.…”
Section: Resultscontrasting
confidence: 73%
See 2 more Smart Citations
“…Ventilation after treatment may reduce the concentration of chemical in the treated room and reduce dispersal [26], yet, our findings suggest that less than half of all individuals using indoor sprays are ventilating rooms during and after applying the sprays. These results are slightly different than the findings from the Northern California SUPERB survey of families with young children, in which 58% reported opening one or more windows during or after application of indoor sprays [16]. This difference could be due to age related factors, or could also be due to the difference in climate between Northern and Central California group.…”
Section: Resultscontrasting
confidence: 73%
“…Indoor insecticides used in the kitchen were most often applied on surfaces less than one square foot (35%) and in several specific areas ranging in size between one and five square feet (30%), only 22% of participants applied product in cracks and crevices. Similar results were seen in Wu et al .’s [16] analysis of SUPERB data for Northern California homes with young children. Keenan et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, household pesticide use and exposure vary by sociodemographic factors such as race/ethnicity and education (35, 36). Similarly, exposure to other substances correlated with adverse child behavioral development, such as bisphenol A or phthalates, can vary by income, with generally higher exposures being seen among lower-income households (37, 38).…”
Section: Discussionmentioning
confidence: 99%
“…A population-based survey of households with young children found that over 80% reported applying some type of insecticide in the previous year [2]. Children have been identified as particularly vulnerable to uptake of pesticides from their environment due to frequent hand-to-mouth behavior, ingestion of soil and dust, mouthing of nonfood items, increased contact with soil, floors and carpets where spray residues settle, and higher concentrations of pesticide residues close to the floor in their breathing zone [3,4,5].…”
Section: Introductionmentioning
confidence: 99%